Thermal diffusivity and 3D-XY critical behavior of ferroelectric semiconductors (PbxSn1−x)2P2Se6. (January 2016) - Shvalya, V.; Oleaga, A.; Salazar, A.; Kohutych, A.A.; Vysochanskii, Yu.M.
Abstract: An ac photopyroelectric calorimeter has been used to study the thermal diffusivity of the ferroelectric semiconductors family (Pb x Sn1− x )2 P2 Se6 ( x =0–1) from 30 K to room temperature. Phase transitions have been found for x =0, 0.05, 0.2, 0.47 but not for x =1 in the full temperature range. A continuous phase transition has been found for x =0, 0.05, 0.2 and 0.47 which corresponds to the paraelectric commensurate to incommensurate phase. It has been possible to study the critical behavior of this transition for x =0, 0.05 and the critical parameters obtained have been α =−0.019, A + / A − =1.00 and α =−0.026, A + / A − =1.03, respectively, having fitted at the same time both the low and high temperature branches of the transition as rigorous critical theory indicates; these results agree with the theoretical prediction from renormalization group theory that this kind of transition complies with the 3D-XY universality class ( α theor =−0.014, A + / A − =1.06), which has been experimentally confirmed only in a few materials. A first order incommensurate to ferroelectric phase transition has been characterized in x =0, 0.05 at lower temperature. Highlights: Thermal diffusivity of (Pb x Sn1− x )2 P2 Se6 is measured from 30 to 300 K. First and second order phase transitions are revealed. Critical behavior of the second order phase transition is studied. It belongs to the 3D-XY universality class, in agreement with theory.